Inflation Pressures and Monetary Policy Options in Emerging and Developing Countries-A Cross Regional Perspective - Otker, Inci (IMF Working Papers; Working Paper ;, 2009)
This paper analyzes the monetary policy response to rising inflation in emerging and developing countries associated with the food and oil price shocks in 2007 and the first half of 2008. It reviews inflation developments in a sample of countries covering all regions and a broad range of monetary and exchange rate policy regimes; discusses the underlying causes of inflation; provides a synthesis of policy responses taken against the background of the conflicting objectives and trade-offs, the uncertainties regarding the nature of the shocks, and the additional challenges brought on by the global financial turmoil; and presents considerations for policy.